Pemeriksaan Ankle Brachial Index (ABI) Post Exercise Pada Pasien Diabetes Melitus dengan Peripheral Arterial Disease - Widyanthari, Desak Made; Sitorus, Ratna; -, Yulia (Coping: Community of Publishing in Nursing, 2016)
The examination of Ankle Brachial Index (ABI) is one method to detect the presence of Peripheral Arterial Disease (PAD) in Diabetic patients. Inaccuracy the diagnosis of PAD results in the inadequate treatment of PAD and this can lead to serious problems such as  amputations, impaired functional capacity, low quality of life and depression. This study aims to determine differences ABI examination Pre and Post Exercise in diabetic patients with intermittent claudication. This study design was  one group pre-post test with  17 samples. The test were analyzed using dependent t test and showed  a significant differences ABI value pre and post exercise on the right foot with  p value of 0.004 and the left foot with  p value of  0.000. This study showed  the measurement of ABI post exercise more objective for the diagnosis of PAD in diabetic  patients with intermittent claudication or suspected PAD.
Keywords: Ankle Brachial Index, Diabetes Melitus, Peripheral Arterial Disease